2014
DOI: 10.1111/aen.12122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aphid feeding and associated virus injury on grain crops in Australia

Abstract: We review yield effects caused by aphid feeding and associated virus injury to cereal, oilseed and pulse crops, and estimate the potential economic loss caused by aphids in Australia. Potential yield reduction due to aphids was determined through a survey of quantitative data from experiments that assessed aphids' effect on grain yield. In cereals, four aphids caused damage; on barley, feeding injury caused by Rhopalosiphum padi + Rhopalosiphum maidis was most damaging in terms of yield reduction (25.5%) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 57 publications
0
41
0
Order By: Relevance
“…The bird cherry‐oat aphid, Rhopalosiphum padi (Linnaeus), is a worldwide agricultural pest of cereals (Leather et al ., ) and a primary vector of economically damaging plant viruses, including Barley Yellow Dwarf Virus ( BYDV ) (Valenzuela & Hoffmann, ). Cereal yield losses due to BYDV infection can reach 35% (Perry et al ., ) and might rise further as R. padi is anticipated to become a more persistent agricultural pest under a changing climate (Finlay & Luck, ).…”
Section: Introductionmentioning
confidence: 99%
“…The bird cherry‐oat aphid, Rhopalosiphum padi (Linnaeus), is a worldwide agricultural pest of cereals (Leather et al ., ) and a primary vector of economically damaging plant viruses, including Barley Yellow Dwarf Virus ( BYDV ) (Valenzuela & Hoffmann, ). Cereal yield losses due to BYDV infection can reach 35% (Perry et al ., ) and might rise further as R. padi is anticipated to become a more persistent agricultural pest under a changing climate (Finlay & Luck, ).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding damage from large M. persicae populations can affect crop establishment, stunt plant growth and reduce crop yields; however, plant virus transmission by M. persicae is generally more economically important. In canola alone, viruses transmitted by M. persicae can reduce crop yields by up to 34% . Furthermore, the secretion of honeydew by aphids can cause secondary fungal growth (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In canola alone, viruses transmitted by M. persicae can reduce crop yields by up to 34%. 4 Furthermore, the secretion of honeydew by aphids can cause secondary fungal growth (i.e. sooty moulds), which inhibits photosynthesis and can further reduce plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Aphids (Hemiptera: Sternorrhyncha: Aphididae) damage crops directly by removing nutrients from sieve elements and act as very efficient vectors of plant diseases (Blackman and Eastop, 2017). A study in Australia demonstrated that the aphid feeding and virus injuries in cereals, oilseed and pulse crops resulted in potential economic costs of $241 and $482 million year −1 , respectively (Valenzuela and Hoffman, 2015). The peach potato aphid Myzus persicae (Sulz.)…”
Section: Introductionmentioning
confidence: 99%